DEVELOPMENT OF THE INNOVATION OF NEW NORMAL LEARNING MODEL TO ENHANCE COGNITIVE SKILLS OF HIGHER EDUCATION STUDENTS IN THAILAND - Kaewsri, Prasit; Aphichando, Phrakru Sangkharak Ekaphatra; Attarung, Thatchathon; Jampawal, Tatila; (Chalermchan), Phramaha Phuean Kittisophano (Journal of MCU Nakhondhat, 2024)
The objectives of this research article were to study the factors that promote the new normal learning model for enhancing the cognitive skills of higher education students in Thailand; and to develop the innovation of the new normal learning model for enhancing the cognitive skills of higher education students in Thailand; The study was qualitative research, the key informants are; 1 expert in Buddhism and education, 2 experts in psychology and education, 2 experts in educational management, and 1 expert in education and educational activities, totaling 6 monk/persons. The research instruments are in-depth interview form and then synthesize data which obtained from studying document and in-depth interview. The research findings were the factors that promote new normal learning model in the form of enhancing cognitive skills of higher education students in Thailand are 1) Attention, 2) Perception, 3) Memory, 4) Thinking methods, and 5) Knowing oneself. The development of the innovation of new normal learning styles to enhance the cognitive skills of higher education students in Thailand, which is the activity package consisting of 6 activities: 1) Dhamma Greetings for the learner’s relaxation, open-minded, preparation for the activity, 2) Searching for the Heart to enhance social skills and Dhamma learning, 3) River of Life to enhance the skills of cognitive and listening, 4) News Searcher to enhance analytical thinking and knowledge sharing, 5) Applying Dhamma to enhance cognitive thinking by reviewing Dhamma and applying Dhamma to daily life and 6) Breath of Learning to enhance mindfulness at the present and self-awareness and others.